Do financial diaries affect financial outcomes? Evidence from a randomized experiment in Uganda. (2018) - Smits, Joeri; Günther, Isabel
Abstract: Survey data on income and expenditure is often of low quality and does not capture the volatile and irregular nature of cash flows of poor households. Financial diaries are increasingly used to improve the precision and accuracy of consumption and income estimates. In this paper we analyze whether keeping track of income and expenditures changes financial behavior and outcomes, which could reduce the validity of diaries as a measurement instrument. Members of urban Ugandan microcredit groups were, through random assignment, offered financial diaries to keep a record of their daily cash flows for more than a year. We find no evidence that financial diaries change numeracy skills, loan repayment, reported income, or food consumption. We only found a difference in savings, but this is unlikely to represent any impact of the financial diaries, as it does not exceed the amount provided as an incentive to the respondent for participation.